ON THE MORAL CONCERNS ABOUT GREEN AI WITHIN THE FRAMEWORK OF DIGITAL HUMANISM. - SERAFIMOVA, SILVIYA (Philosophical Alternatives Journal / Filosofski Alternativi, 2025)
The major objective of this article is to clarify how one can build a holistic philosophical approach to Green AI that can foster humancentered synergy with technology in moral terms within the framework of the so-called Digital Humanism. Specifically, I examine both the origin and the implications of some moral concerns about Green AI as a multi-agent system by focusing on the complex understanding of AI sustainability. In this context, the latter is recognized as resulting from the cultivation of intra- and intergenerational environmental justice, when one is guided by the Digital Humanim’s core principle of prioritizing human values over these of technologies.